Islamic Financial Management Training for MSMEs of The Congregation of Mosque Under The Auspices of The Indonesian Mosque Council Surabaya - Nurafini, Fira; Canggih, Clarashinta; Indrarini, Rachma; Munir, Maryam Bte Badrul (MOVE: Journal of Community Service and Engagement, 2025)
Mosques are places of worship that not only serve as centers for religious practices but also play an active role in community muamalah (socio-economic) activities. The Indonesian Mosque Council (DMI), a partner of the Islamic Economics Study Program Universitas Negeri Surabaya, is a national-level organization dedicated to realizing the role of mosques as centers for worship, community development, and unity. The Islamic Economics Study Program Universitas Negeri Surabaya collaborates with DMI Karang Pilang to implement community service programs aimed at developing mosques and their congregations in the DMI Surabaya. This community service program targets MSME (Micro, Small, and Medium Enterprises) actors who are mosque congregants, as well as congregants who intend to start businesses at mosques under the supervision of DMI Surabaya, located in the Karang Pilang District. The program's activities include workshops and socialization sessions focused on the importance of sharia-compliant financial management for MSMEs and practical guidance on implementing financial management in accordance with sharia. The expected outcome of this program is that MSME actors and congregants intending to start businesses will gain a comprehensive understanding of proper financial management and successfully apply it, thereby preparing them to navigate the challenges of uncertain economic conditions.